Kinetics of Oxidation of p-Iodoaniline by Chromic Acid - Mishra, Sudheer; Shrivastava, K.B.L. (Asian Journal of Chemistry, 2012)
The kinetics of the chromic acid oxidation of p-iodo aniline have been studied in 10% aqueous acetic acid medium. The order with respect to both oxidant and substrate is one in each case. The order of reaction with H+ is one in each case. The reaction velocity increases by increasing the percentage composition of acetic acid. The primary salt effect on the rate of oxidation is negligible. The catalysts such as Ag+, Cu2+ show increasing effect whereas Mn2+ retards the rate. Various thermodynamic parameters have been evaluated. A probable mechanism has been suggested on the basis of kinetic results.